Exploring the Potential of online English Websites In Teaching English To Non-Linguistic Major Students: BreakingNewsEnglish As Example - Boulahnane, Saad; Abramova, Viktoriia S. (Register Journal, 2019)
The Internet has captured the attention of teachers and language instructors from all over the world due to its online teaching materials. The Internet-based material has allowed distance-learning projects. This article explores the potential role of EFL websites as a supplement in classroom instruction. As an example, an English-language based news website, www.breakingnewsenglish.com, has been designed to teach English to non-linguistic major students. The authors of this article offer methodological recommendations on using Internet-based materials, describe stages of work with authentic texts, and note linguistic and communicative skills developed in the course of work. The recommendations have been formed based on teachers and students’ descriptions of the materials provided by the website in question. This descriptive article will hopefully contribute to the literature on online teaching and learning materials, particularly in the field of EFL.Keywords: foreign languages, online educational resource, news website, communicative skills